The Effect Of Work Environment, Work Motivation, And Work Discipline On The Performanceof Employees Of The Department Of Tourism, Youthand Sports Of Seluma Regency - Putriani, Ririn; Anggriani , Ida; Effendi , Bahman (Jurnal Pusat Manajemen, 2025)
The purpose of this study was to determine the influence of work environment, work motivation, and work discipline on employee performance at the Department of Tourism, Youth and Sports of Seluma Regency. The method used is a quantitative method where data is obtained by distributing questionnaires to all employees with Civil Servant status at the Department of Tourism, Youth and Sports of Seluma Regency, totaling 42 people. The results of the analysis show that the work environment does not have a significant effect on employee performance. While work motivation and work discipline have a significant effect on employee performance at the Department of Tourism, Youth and Sports. With the results of multiple linear regression tests on showing the equation; Y = 2.188 - 0.040 (X1) + 0.517 (X2) + 0.456 (X3) + e, the coefficient of determination (R square) value of SPSS Version 25 is 0.699 which means X1, X2 and X3 have an effect of 69.9% on employee performance at the Department of Tourism, Youth and Sports of Seluma Regency, while the remaining 30.1% is influenced by other variables. The results of the t-test at a significance level of 0.05 explain that partially X1 has no significant effect on Y with a value of 0.719 > 0.05, X2 has a significant effect on Y with a value of 0.007 < 0.05 and X3 has a significant effect on Y with a value of 0.001 < 0.05. Based on the F test, Work Environment, Work Motivation and Work Discipline have a simultaneous effect on the Performance of Employees of the Seluma Regency Tourism, Youth and Sports Office with a result of 0.000 < 0.05.